Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di Dealer Daihatsu Maumere - Petrus Carolus Tari Sedo; Andreas Rengga; Nunsio H. Meylano (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This study aimed to analyze the effect of product quality and service quality on customer satisfaction. The objectives of this study include an overview of product quality,service quality, and customer satisfaction at Daihatsu Maumere dealership, as well as identifying the effect of product quality on customer satisfaction and to determine the effect of service quality on customer satisfaction, and the simultaneous effect of product quality and service quality on customer satisfaction at Daihatsu Maumere dealership.This research employed quantitative research where the data used in the research was primary data obtained directly in the field through interviews or questionnaires.The analysis method used was multiple linear regression analysis that aimed to test the relationship between product quality and service quality on customer satisfaction. The results showed that product quality had an impact on customer satisfaction. Service quality had a significant impact on customer satisfaction. In addition, the simultaneous analysis showed that product quality and service quality had a simultaneous effect on customer satisfaction.